1993
DOI: 10.1016/0370-2693(93)90998-w
|View full text |Cite
|
Sign up to set email alerts
|

Charge-symmetry breaking, rho-omega mixing, and the quark propagator

Abstract: The momentum-dependence of the ρ 0 -ω mixing contribution to chargesymmetry breaking (CSB) in the nucleon-nucleon interaction is compared in a variety of models. We focus in particular on the role that the structure of the quark propagator plays in the predicted behaviour of the ρ 0 -ω mixing amplitude. We present new results for a confining (entire) quark propagator and for typical propagators arising from explicit numerical solutions of quark Dyson-Schwinger equations. We compare these to hadronic and free q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 24 publications
7
85
0
Order By: Relevance
“…It is convenient because only the chiral limit amplitudes need to be modelled. With the m = 0 forms of A and B extracted from (11) and (12) The momentum dependence obtained is quite similar to that found in earlier work [5,6]. The experimental mass-shell mixing strength was produced in the work of Ref.…”
Section: Isovector Component Of the Quark Propagator And ρ 0 -ω Mixingsupporting
confidence: 81%
“…It is convenient because only the chiral limit amplitudes need to be modelled. With the m = 0 forms of A and B extracted from (11) and (12) The momentum dependence obtained is quite similar to that found in earlier work [5,6]. The experimental mass-shell mixing strength was produced in the work of Ref.…”
Section: Isovector Component Of the Quark Propagator And ρ 0 -ω Mixingsupporting
confidence: 81%
“…As examples we note that the model has been used successfully to calculate the ω-ρ mass splitting induced by ρ → ππ → ρ, ρ → ωπ → ρ, ω → ρπ → ω and ω → πππ → ω self energy corrections (Hollenberg et al, 1992) and to analyse the contribution of pion loops to the electromagnetic charge radius of the pion , which is found to be an additive correction to r 2 π of < 15% at m π = 0.14 GeV. Furthermore, recent calculations of the ω-ρ mixing component of the N-N potential (Goldman et al, 1992;Krein et al, 1993;Mitchell et al, 1994) also fit neatly within this framework. The important feature of these meson-loop contributions is that they too are finite because the Bethe-Salpeter amplitudes that describe the quark core of the hadrons appear in every integral and provide natural momentum cutoffs, thus ensuring convergence.…”
Section: Effective Actions and Qcdmentioning
confidence: 99%
“…The plausibility of this explanation (which employs the observed mixing, measured at q 2 = m 2 ω , unchanged in the spacelike region q 2 < 0) has, however, recently been called into question by Goldman, Henderson and Thomas [6] who pointed out that, in the context of a particular model, the relevant ρ − ω mixing matrix element has significant q 2 -dependence. Subsequently, various authors, employing various computational and/or model framewords, have showed that the presence of such q 2 -dependence appears to be a common feature of isospin-breaking in both meson-propagator-and current-correlator matrix elements [7][8][9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%